2021
DOI: 10.3389/fcell.2021.622539
|View full text |Cite
|
Sign up to set email alerts
|

Human Wharton’s Jelly Mesenchymal Stromal Cell-Derived Small Extracellular Vesicles Drive Oligodendroglial Maturation by Restraining MAPK/ERK and Notch Signaling Pathways

Abstract: Peripartum cerebral hypoxia and ischemia, and intrauterine infection and inflammation, are detrimental for the precursor cells of the myelin-forming oligodendrocytes in the prematurely newborn, potentially leading to white matter injury (WMI) with long-term neurodevelopmental sequelae. Previous data show that hypomyelination observed in WMI is caused by arrested oligodendroglial maturation rather than oligodendrocyte-specific cell death. In a rat model of premature WMI, we have recently shown that small extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Also, Hippo signaling cascade was found to be associated with the pubertal development of male reproductive tract and spermatogenesis in sheep ( Zhang et al, 2019 ). MAPK signaling pathway is the key mediator that controls the phosphorylation of many downstream effectors, leading to modulate different cellular functions, including cell proliferation, differentiation, and migration ( Joerger-Messerli et al, 2021 ). Oxidative stress-mediated p38 MAPK signaling pathway was associated with the blood-testis barrier-related junction protein and promoting apoptosis in mice testes ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Hippo signaling cascade was found to be associated with the pubertal development of male reproductive tract and spermatogenesis in sheep ( Zhang et al, 2019 ). MAPK signaling pathway is the key mediator that controls the phosphorylation of many downstream effectors, leading to modulate different cellular functions, including cell proliferation, differentiation, and migration ( Joerger-Messerli et al, 2021 ). Oxidative stress-mediated p38 MAPK signaling pathway was associated with the blood-testis barrier-related junction protein and promoting apoptosis in mice testes ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on the direct interaction between human stem cells and oligodendroglia. A recently published study by Joerger-Messerli provided evidence that human extracellular vesicles derived from WJ-MSCs interacted with the MO3.13 cell line and accelerated their maturation after 5 days of co-culture [54]. In our study, we observed secretion of cytokines/chemokines/growth factors after 2 days of cell-to-cell contact of WJ-MSCs and MO3.13 and showed significant inhibition of MSCs secretory activity, which might be related to initiation of differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The normal expression of OLIG2 contributes to the developmental regulation of oligodendrocytes precursor cells and the early directed differentiation to OLs. OLs are widely distributed in the central nervous system, which contribute to the formation of myelin sheath and could be impaired by neuroinflammation ( Xie et al, 2016 ; Huntemer-Silveira et al, 2020 ; Joerger-Messerli et al, 2021 ). In this study, we confirmed PND increased the expression of WNT10B and β-catenin and decreased the expression of OLIG2.…”
Section: Discussionmentioning
confidence: 99%